2021
DOI: 10.1001/jama.2021.7621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cytisine vs Varenicline on Smoking Cessation

Abstract: IMPORTANCE Cytisine is more effective than placebo and nicotine replacement therapy for smoking cessation. However, cytisine has not been tested against the most effective smoking cessation medication, varenicline, which is associated with adverse events known to lead to discontinuation of therapy.OBJECTIVE To examine whether standard cytisine treatment (25 days) was at least as effective as standard varenicline treatment (84 days) for smoking cessation. DESIGN, SETTING, AND PARTICIPANTSThis noninferiority, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 29 publications
1
45
0
3
Order By: Relevance
“…Cytisine is a plant alkaloid that has nicotine-like effects, while at the same time blocking the effects of nicotine, similar to varenicline [86]. Clinical trials show efficacy comparable with other first-line smoking cessation medications, with relatively few adverse effects [87][88][89]. This drug is licensed in eastern Europe, but not in the United States or in many other countries.…”
Section: Newer Medicationsmentioning
confidence: 99%
“…Cytisine is a plant alkaloid that has nicotine-like effects, while at the same time blocking the effects of nicotine, similar to varenicline [86]. Clinical trials show efficacy comparable with other first-line smoking cessation medications, with relatively few adverse effects [87][88][89]. This drug is licensed in eastern Europe, but not in the United States or in many other countries.…”
Section: Newer Medicationsmentioning
confidence: 99%
“…Participants from Sydney and the wider catchment region are recruited predominately through study advertisements across online and social media platforms such as Facebook advertisements. Participants in a recently completed clinical trial comparing cytisine versus varenicline for smoking cessation who consented to being contacted about future research and were receiving a government pension were also invited to take part [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…At low doses, cytisine activates nAChRs in the mesolimbic reward pathways and that inhibits nicotine’s sensory stimulation and limits the symptoms of withdrawal [ 103 ]. Cytisine was not only noninferior to NRT but had superior effectiveness [ 104 ]; however, in a recent study, varenicline was found more effective [ 105 ]. Varenicline is a partial α4β2 agonist that has all the characteristics of cytisine but is more efficient with fewer side effects [ 106 ].…”
Section: Smoking Cessation Treatments and Osamentioning
confidence: 99%